2021
DOI: 10.3390/ani11010161
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Presence of Domestic Dogs on Sandy Beaches of Southern Chile

Abstract: Dogs on sandy beaches are a threat to shorebirds. Managing this problem requires understanding the factors that influence the abundance of dogs in these ecosystems. We aimed to determine the proportion of beaches used by dogs and the effects of human presence on dog abundance on sandy beaches of southern Chile. We conducted dog counts and recorded the presence of tracks on 14 beaches. We used zero-inflated generalized linear mixed models to determine if the number of people, number of households, and other cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 60 publications
0
9
0
2
Order By: Relevance
“…Worryingly, RNA sequencing has shown signs of early adaptation of the H5N1 2.3.4.4b clade virus to wild mammals (Vreman et al 2023) and humans (Centers for Disease Control and Prevention 2023), fueling the fears of a new human pandemic (Kupferschmidt 2023). In addition, recent reports of a dog and two cats dying from H5N1 after contact with dead birds in North America (Canadian Food Inspection Agency 2023) rises the potential of wildlife to dog transmission in South American countries like Chile, where a high population of dogs (both owned and stray) occurs on the coast (Cortés et al 2021). Even more, two cases of zoonotic avian influenza have recently been reported in South America (Ecuador and Chile), with the Chilean case being of special concern.…”
Section: Discussionmentioning
confidence: 99%
“…Worryingly, RNA sequencing has shown signs of early adaptation of the H5N1 2.3.4.4b clade virus to wild mammals (Vreman et al 2023) and humans (Centers for Disease Control and Prevention 2023), fueling the fears of a new human pandemic (Kupferschmidt 2023). In addition, recent reports of a dog and two cats dying from H5N1 after contact with dead birds in North America (Canadian Food Inspection Agency 2023) rises the potential of wildlife to dog transmission in South American countries like Chile, where a high population of dogs (both owned and stray) occurs on the coast (Cortés et al 2021). Even more, two cases of zoonotic avian influenza have recently been reported in South America (Ecuador and Chile), with the Chilean case being of special concern.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the clear effect of disturbances on foraging Godwits suggests the need for real protective measures. Reducing the numbers of humans and dogs on tidal mudflats, in particular, would increase foraging success rates by reducing nonlethal effects (Navedo et al 2019, Cort es et al 2021. Although the movements of Godwits among sites on the island are poorly understood, targeting areas of high prey abundanceas indicated by Godwit foraging success rateswithout restricting the use of tidal mudflats with lower prey abundance, could benefit Godwits while minimizing the socio-economic effects for residents (Weston et al 2012, Stigner et al 2016.…”
Section: Alertness and Agitationmentioning
confidence: 99%
“…The overlap in space and time with perceived or actual threats from human activity or predators can influence the abundance, behaviour, distribution and condition of individual migrants (Goss-Custard et al 2020, Hope et al 2020. Migratory shorebirds often reduce risk by being vigilant, assembling in large groups (Cresswell 1994a, Bednekoff & Lima 1998 or avoiding risky areas, such as those frequented by predators (Pomeroy 2006, Yasu e 2006, humans (Frid & Dill 2002) or dogs (Burger et al 2007, Cort es et al 2021. Predators not only threaten survival but also can displace individuals and reduce the amount of time spent foraging by increasing scanning for predators (Yasu e 2005, Burger et al 2007, Alves et al 2013, Schlacher et al 2014, thereby impacting body condition (Goss-Custard et al 2006).…”
mentioning
confidence: 99%
“…Recently, Saavedra-Aracena et al demonstrated that the dog–owner bond, particularly the exploration behavior in the absence of the owner, explained further roaming [ 23 ]. Research on the human–dog link determined that free-ranging dogs tend to follow persons other than their owners [ 29 , 30 ]. Therefore, might tourists, who target green destinations, specifically attract dogs to nature?…”
Section: Introductionmentioning
confidence: 99%